Penilaian Green Building pada Aspek Indoor Health Comfort, Energy Efficiency and Conservation pada Bangunan Gedung (Studi Kasus: Gedung X di Bandar Lampung) - M Ridho Bagas Tri Amarta AN; Putty Yunesti; Khoirun Naimah (Jurnal Engine: Energi, Manufaktur, dan Material, 2026)
The concept of green building emerged and has been promoted as a solution to reduce the impact of carbon footprints. It has evolved into an integrated approach to environmentally friendly and sustainable building design, construction, and operation. The objective of this study is to evaluate the implementation of green building principles, assess the level of achievement in meeting green building criteria, and provide recommendations for improvements to help buildings meet the standards set by the Green Building Council Indonesia (GBCI) through its Greenship rating system. This research employed methods including observation, interviews, and measurements, with the results analyzed using a descriptive approach. The assessment of Building X in Bandar Lampung revealed that it scored only 10 out of a maximum of 20 points (equivalent to 45%) for the Indoor Health and Comfort category, and 16 out of a maximum of 36 points (equivalent to 44.4%) for the Energy Efficiency and Conservation category. To improve the green building performance scores, several measures can be undertaken. These include the installation of monitoring instruments for temperature, carbon dioxide, and carbon monoxide levels; indoor air quality assessments; optimization of lighting systems; formation of an energy cluster team; enhanced energy efficiency and conservation strategies; the use of renewable energy sources such as solar panels; and the provision of sub-metering (kWh meters) for ventilation, lighting, and other electrical systems.